Natural antibodies in paracoccidioidomycosis - Unterkircher,Carmelinda S. (2004)
Recent attention has been focused on the natural antibodies as a component of natural immunity and as integral part of the idiotypic network. However, their functional role in different infections has rarely been studied. This work was undertaken to investigate the presence of natural antibodies in paracoccidioidomycosis (PCM). In addition, we analyzed anti-P. brasiliensis antibodies and their distribution in IgG subclasses in order to acquire better knowledge about the humoral immune response in this mycosis. Our findings show that the natural antibody response is not very much increased in PCM when compared with other parasite infections and this response is restricted to a few specificities, suggesting that P. brasiliensis moderately triggers CD5+ B cells. The anti-actin antibody was the main antibody specificity found in PCM. Specific antibodies to P. brasiliensis were mainly found in the IgG1 subclass in chronic patients of PCM.